O contágio dos afetos: rupturas, deslocamentos e permanências em uma travessia pela prisão - Cougo, Vitória Rosa (2021)
This result is the result from concerns, ruptures, displacements and permanence in the clash between the theory about prisional institutions and the experiential affectation that the researcher lived in contact with prisoners and workers from the Presídio Estadual de Júlio de Castilhos (PEJULI). Above all, it is a journey that contests research practices and the constitution of the being-researcher in a prison institution, allowing the researcher to affect herself emotionally in the encounter with the prisoners' narratives, as well with the space-time from the prison. In a constant inquiring about the frameworks and imprisionments that also permeate the academic world, the paths chosen by the researcher provide opportunities for a more humanity relationship and closer to a subjective narrative to research's act. The crossing of a historical pandemic scenario in the course of this research provided an opportunity for the eruption of powerful meeting points between inside and outside the prison - previously unthinkable - resulting from the generalization and accentuation of vulnerability and interdependence - ontological conditions of human life. It is understandable that the development from this social scenario helped to developed this dissertation the expansion of est (ethical) -political movements that were made in the testimony of the researcher's encounter with prisoners from PEJULI through new frames.The work has its reflections on the opening of gaps and passages for the thinking of existential aspects shared between the prison world and life in contemporary capitalist society.